PERISTIWA TUTUR DAN TINDAK TUTUR ANTARA DOSEN DENGAN MAHASISWA - Siboro, Efibora; Citra Mutiara Pasaribu; Buana Pane; Eka Panjaitan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study examines speech events and speech acts in academic interactions between lecturers and students during a thesis proposal seminar. Using a qualitative approach with audio recordings and observation, data were collected from classroom interactions and transcribed for analysis. The analysis employs Hymes’ SPEAKING model and Searle’s speech act theory to explore the structure, intent, and social dynamics of academic communication. Results show that speech events in formal academic settings are characterized by structured sequences, hierarchical roles, and adherence to academic norms. Lecturers predominantly use directive and evaluative speech acts, while students employ assertive and commissive acts to defend their proposals. The study highlights how language functions as a tool for evaluation, argumentation, and knowledge construction within the academic context. Findings emphasize the relationship between social power, communicative purpose, and linguistic choice in educational interactions.